A LARGE AGGRESSIVE PHOSPHATURIC MESENCHYMAL TUMOR OF THE HUMERUS: SURGICAL MANAGEMENT AND BUROSUMAB THERAPY FOR TUMOR-INDUCED OSTEOMALACIA - Harindhanavudh, Tasma; Espejo-Freire, Andrea; Murugan, Paari; Cheng, Edward (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Tumor-induced osteomalacia (TIO) is a rare condition caused by phosphaturic mesenchymal tumors (PMTs) that overproduce FGF23, resulting in renal phosphate wasting. We present a case of a 74-year-old female with a right humeral fracture. MRI revealed a large (6.4x7.2x8.2 cm) enhancing lesion in the proximal right humerus, confirmed as a PMT by core biopsy. Laboratory findings showed persistent hypophosphatemia and FGF23 levels >30,000 pg/mL. The PMT was excised, and impaction bone allograft fixation was performed. Pathology results indicated a non-malignant tumor but with features warranting concern. The PET scan showed no metastatic disease, and residual tumor was suspected as the cause of persistent hypophosphatemia. Postoperatively, burosumab, an antibody targeting FGF23, was initiated to restore phosphorus levels and alleviate bone pain. This case underscores the complexity of managing TIO with a large PMT, necessitating a multidisciplinary approach involving various specialties. Burosumab demonstrates promise as an effective treatment option when surgical intervention alone may be insufficient.